Implementasi Penyelenggaraan Pendidikan Dalam Perspektif Indeks Kepuasan Masyarakat (IKM) - Asrori Asrori (TADARUS, 2014)
Abstrak This research is based on the phenomenon of the education and how the school role as an education organizing office can give the education service well. It encourages the government to do the improvement in Indonesia education system with education decentralittion policy was formed in “School Based management, that there are several functions done by a school independently, so that a school given otonomy to organize the school resources. Key Words: Implementation, Education Management, Perpective Index Society Satisfaction.